La mobilità intelligente: miglioramento del well-being e salvaguardia dell’ecosistema - Helena Biancuzzi; Francesca Dal Mas; Maurizio Massaro; Carlo Bagnoli (European Journal of Volunteering and Community-Based Projects, 2024)
Purpose: The article aims to investigate the actors who generate ecosystem value, the stakeholders who capture it, the concept of value generated/captured, focusing on the field of Smart Mobility (SM). This sector represents a critical context for analyzing possible innovative landscapes in terms of sustainability. The paper studies SM in the Italian city of Venice, the world capital of sustainability.